Studi Religiusitas, Budaya Sunda, dan Perilaku Moral pada Masyarakat Kabupaten Bandung - Ujam Jaenudin; Tahrir Tahrir (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2019)
This research was based on the phenomenon of religiosity and the application of Sundanese cultural values in Bandung. The purpose of this study is to determine the effect of Sundanese resilience and culture on moral behavior. The design of this study uses a causality design that aims to determine how much influence one variable has on another. The total sample were 100 villagers. The data was collected using a set of questionnaire of religiosity, Sundanese culture, and moral behaviour, with Likert model. Hypothesis was tested using regression. The findings show that religiosity and Sundanese culture have positive and significant effect on moral behavior.